Education, Person and Politics. Intuitions and tensions in Paulo Freire (Cultura Económica, 2018)
In this article we propose revisiting the work of Paulo Freire in dialogue with educational personalism. Throughout his intellectual career we find an element that favors this dialogue, the centrality of the person in Freire’s practice and pedagogical theory. However, we also find an issue that may contradict personalism: the question of the essentially political character of education. Through a philosophical analysis that goes back to the metaphysical foundations of Freirean approach, we will try to determine the viability of the proposed dialogue with personalism.
Keywords: PAULO FREIRE; PERSONALISM; EDUCATION; POLITICS